Eletroacupuntura reduz hiperalgesia em modelo animal de hiperalgesia induzida por dupla injeção de salina hipertônica - Maciel, Leonardo Yung dos Santos (2012)
Repeated injections of acidic saline into the gastrocnemius muscle in rats produce a bilateral long-lasting hiperalgesia similar to fibromyalgia syndrome in humans. After the induction, it´s possible to test the efficacy of analgesic strategies such as electroacupuncture and acupuncture. This study aimed to identify the effects of acupuncture and electroacupuncture in the hyperalgesia produced by repeated intramuscular injections of acidic saline. Twenty four male Wistar rats were divided into four groups (n = 6, in each group): control, acupuncture, electroacupuncture (EA) 15 Hz and (EA) 100 Hz. Left gastrocnemius muscle from all animals was injected with 100 μL of pH 4.0 sterile saline twice five days apart. Electroacupuncture, acupuncture or control was daily administered (20 min) for 5 consecutive days under isoflurane anesthesia (2% 5%). Needles were placed in the Zuzanli (St36) and Sanyinjiao (SP6). We assessed the secondary mechanical hyperalgesia, thermal hyperalgesia and motor performance before the two injections, and before and after the treatment each day. The results indicate that there was a significant reduction of both mechanical withdrawal threshold and paw withdrawal latency 24 hours following the second injection. Therefore, both mechanical and thermal hyperalgesia were significantly reversed by EA 15 Hz, EA 100 Hz and acupuncture. It can be suggested that as high and low frequency eletroacupuncture as acupuncture is effective in hiperalgesia reducing in this model of chronic muscle pain.